UI Green Metric World University Rankings - UiTM, UGC (UiTM Green Centre, 2025)
SHAH ALAM, 5 December 2025 – Universiti teknologi mara (UiTM) has made history by breaking into the world’s top 100 institutions for the first time, securing the 94th position in the UI Green Metric World University Rankings 2025. This achievement signals a significant 13-place improvement, placing UiTM firmly within the top 5% of 1,745 institutions worldwide and ranking 5th in Malaysia. This is UiTM's best performance to date since its first participation in the ranking in 2019. UiTM's advancement this year is driven by outstanding performance in water and waste categories, reflecting the university's steadfast commitment to sustainable resource governance and the successful execution of its green campus initiatives. With this year’s cycle marking the highest participation on record, UiTM's ascent validates its rising prominence in the global sustainability landscape. UiTM Vice-Chancellor, Professor Datuk Ts. Dr Shahrin bin Sabih @ sahibuddin expressed deep appreciation for the collective effort that propelled UiTM to this milestone. “Alhamdulillah. Achieving a world top 100 position is a powerful testament to UiTM’s commitment to greenation and the dedication of our entire community. This recognition reinforces our resolve to advance UiTM's leadership in environmental stewardship in Malaysia and beyond.”